Personal Differences among Brazilian Adolescents with Distinct Levels of Engagement in Delinquency - Vilela Komatsu, André; Rezende Bazon, Marina (International Journal of Criminology and Sociology, 2017)
Many adolescents manifest delinquent behavior, but only a few are responsible for most of the offenses and the serious crimes. To know the differences in the criminal engagement and in the personal variables related to the more persistent/severe antisocial behavior is important to adjust the Juvenile Justice Systems to the adolescents needs. In the Brazilian Justice System, this is not considered. Although the law indicates the importance of personalizing legal and social responses to each juvenile offender, the treatment is essentially undifferentiated. Therefore, the purpose of this study was to identify and describe personal variables that discriminate subgroups of Brazilian adolescents with different levels of criminal engagement. A total of 193 male adolescents (133 recruited in schools and 60 institutionalized) answered a Self-Report Delinquency Questionnaire, which included scales of psychosocial constructs. Five groups were found by the Ward and K-means clustering methods. The adolescents were compared on variables such as personal traits. Those groups with major criminal engagement had higher levels of impulsivity (η² = 0.08; p = 0.002), higher antisocial values (η² = 0.08; p = 0.003), and higher prevalence of alcohol (X² = 103.75; p < 0.001) and marijuana use (X² =257.61; p < 0.001). This finding confirms the specialized literature, denoting how important it is to identify and understand the differences in the criminal engagement of adolescents.